Sala de aula invertida no ensino de Química aplicada de forma remota: aspectos socioeconômicos, socioemocionais e ganho de Hake - Sampaio, Francisca Kelly Araujo Leite (2022)
Active methodologies are teaching and learning methods that aim at the development of autonomy and the participation of students in an integral and active way in the construction of knowledge, innovating the traditional approach. Among the active methodologies, the Flipped Classroom proposes access to content before class, emphasizing the use of technologies for knowledge acquisition, resulting in active learning during class through personalized education tailored to the individual needs of the student. This study analyzed the impacts on the teaching and learning process of applying the Flipped Classroom associated with the methodology Just-in-time Teaching (JiTT), adapted for remote form, in two high schools, under the Electrochemistry content approach, during the Covid-19 pandemic. The socio-economic and socio-emotional aspects of the students and the perceptions of the teachers involved were also rated. For the application of Flipped Classroom, copyrighted video classes available on YouTube were used. Activity forms monitored student participation and, according to the method JiTT, helped in the preparation of personalized remote classes, as well as in the construction of a formative assessment. Active participation was encouraged through debates and discussions that made it possible to deepen the contentes. The learning implications were evaluated by the variation in the percentage of correct answers in the conceptual tests before (Spré) and after (Spós%) the application of Flipped Classroom. The results showed a positive Hake Gain: 0,41 to School-A and 0,29 to School-B, reflecting in learning gain in relation to the students' initial knowledge. Some parameters contributed to justify this difference, such as a higher level of education of the parents and better condition of students at School-A, in addition to the fact that they are more familiar with the use of video classes. Also, in this school, the impacts of the pandemic were less accentuated and its students showed the best levels of development in 3 socio-emotional competences (organization, self-confidence and curiosity). The perceptions of teachers about the Flipped Classroom, were positive, revealing a willingness to innovate in their classes, despite the need for better compression on the topic. In general, the Flipped Classroom promoted a conceptual gain in student learning, stimulating the development of autonomy and protagonism, offering a change in the school environment and its participants, putting the student at the center of the teaching and learning process.